2016
DOI: 10.1007/s10856-016-5679-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal behaviour of an acrylic bone cement modified with a triblock copolymer

Abstract: The basic formulation of an acrylic bone cement has been modified by the addition of a block copolymer, Nanostrength(®) (NS), in order to augment the mechanical properties and particularly the fracture toughness of the bone cement. Two grades of NS at different levels of loading, between 1 and 10 wt.%, have been used. Mechanical tests were conducted to study the behaviour of the modified cements; specific tests measured the bend, compression and fracture toughness properties. The failure mode of the fracture t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Other authors have reported an increase in the amount of residual monomer with the incorporation of GO [20] and CS. Despite the rise, these values are lower than those reported in other studies [20,31] and are similar to those reported by Islas-Blancas et al [32], who affirm that they are within the range observed for commercial cement [33].…”
Section: Resultssupporting
confidence: 88%
“…Other authors have reported an increase in the amount of residual monomer with the incorporation of GO [20] and CS. Despite the rise, these values are lower than those reported in other studies [20,31] and are similar to those reported by Islas-Blancas et al [32], who affirm that they are within the range observed for commercial cement [33].…”
Section: Resultssupporting
confidence: 88%
“…used commercially available PMMA‐PBuA block copolymers ( Nanostrength M52 from Arkema) in PMMA. [ 27 ] However, no significant toughness enhancing effect was observed, most likely due to unsuccessful microphase separation in the acrylate resin system. Also for peroxide‐cured, unsaturated polyesters, modifications with commercially available poly(ethylene oxide)/poly(propylene oxide) PEO‐PPO‐PEO block copolymers ( Pluronics from BASF) were accompanied by only a rather small increase in fracture toughness but a sharp drop in modulus.…”
Section: Introductionmentioning
confidence: 99%
“…[24] The poly(ethylene oxide)-b-(butylene oxide) (PEO-PBO) diblock copolymer, commonly known as Fortegra 100 from Olin Corporation, [25] is particularly efficient. Other examples include Arkema's Nanostrength series based on poly(methyl methacrylate)-poly(butyl acrylate) (PMMA/PBuA) blocks [26,27] or BCPs based on polycaprolactone-polydimethylsiloxane (PCL-PDMS). [28] In epoxy resins, an increase of the work of fracture of up to 20 times in comparison to unmodified resin was mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…192 Moreover, the incorporation of a commercial block copolymer, Nanostrength ® (NS), into the liquid phase of the PMMA bone cement has been shown to improve the fracture toughness of the cement. 194 Table 4 lists some other alternative PMMA cement formulations and briefly summarizes key findings of the cited studies.…”
Section: Some Alternative Formulationsmentioning
confidence: 99%